A Nitrogen-Fixing Subunit Essential for Accumulating 4Fe-4S-Containing Photosystem I Core Proteins . Issue 4 (26th October 2016) - Nath, Krishna; Wessendorf, Ryan L.; Lu, Yan
Abstract : Loss-of-function mutants of a chloroplastic nitrogen-fixation-subunit-U-type protein showed decreased accumulation of 4Fe-4S-containing photosystem I core proteins. Abstract: Nitrogen-fixation-subunit-U (NFU)-type proteins have been shown to be involved in the biogenesis of iron-sulfur clusters. We investigated the molecular function of a chloroplastic NFU-type iron-sulfur scaffold protein, NFU3, in Arabidopsis ( Arabidopsis thaliana ) using genetics approaches. Loss-of-function mutations in the NFU3 gene caused yellow pigmentation in leaves, reductions in plant size, leaf size, and growth rate, delay in flowering and seeding, and decreases in seed production. Biochemical and physiological analyses indicated that these defects are due to the substantial reductions in the abundances of 4Fe-4S-containing photosystem I (PSI) core subunits PsaA (where Psa stands for PSI), PsaB, and PsaC and a nearly complete loss of PSI activity. In addition to the substantial decreases in the amounts of PSI core proteins, the content of 3Fe-4S-containing ferredoxin-dependent glutamine oxoglutarate aminotransferases declined significantly in the nfu3 mutants. Furthermore, the absorption spectrum of the recombinant NFU3 protein showed features characteristic of 4Fe-4S and 3Fe-4S clusters, and the in vitro reconstitution experiment indicated an iron-sulfur scaffold function of NFU3. These data demonstrate that NFU3 is involved in the assembly and transfer of 4Fe-4S and 3Fe-4S clusters and that NFU3 is required for the accumulation of 4Fe-4S- and 3Fe-4S-containing proteins, especially 4Fe-4S-containing PSI core subunits, in the Arabidopsis chloroplast.